Sleep disturbance in children and adolescents with disorders of development : (Mac Keith Press, 2001)
Sleep disturbance is extremely common in the various disorders of development, be they physical or psychological in nature. It adds significantly to the burden of care but is a neglected topic and there is no single source of information to guide practice and management. In this book an international team of experts provides for the first time an integrated, comprehensive and up-to-date review of the nature and causes of sleep disorders, describing the special assessment and management considerations for each of the different developmental disorders. The book will be essential reading for all professionals working in the area of developmental disorders, and will also be of considerable interest to teachers, social workers and parents.